Multiharmonic Frequency Tracking Method Using The Sigma-Point Kalman Smoother. (22nd March 2010) - Kim, Sunghan; Paul, Anindya S.; Wan, Eric A.; McNames, James
Abstract : Several groups have proposed the state-space approach to tracking time-varying frequencies of multiharmonic quasiperiodic signals. The extended Kalman filter/smoother (EKF/EKS) is one of the common frequency tracking approaches seen in the literature. We introduce a multiharmonic frequency tracker based on the forward-backward statistical linearized Sigma-Point Kalman smoother (FBSL-SPKS) and compare its performance to that of the extended Kalman smoother (EKS). In all cases the FBSL-SPKS tracker outperformed the EKS tracker over a wide range of signal-to-noise (SNR) ratios. We also demonstrate its superior performance on real signals.